"I Would Never Fall for That": The Use of an Illegitimate Authority to Teach Social Psychological Principles. (April 2019) - Farley, Sally D.; Carson, Deborah H.; Pope, Terrence J.
This activity explores attitudinal beliefs and behavioral responses of obedience to an illegitimate authority figure in an ambiguous situation. In Experiment 1, students either self-reported the likelihood that they would obey a request made by a stranger to surrender their cell phone or were asked directly and in person by a confederate to relinquish their cell phone. The exercise revealed a marked discrepancy between how students predicted they would respond and how they actually did respond to the request. In Experiment 2, student learning was measured in addition to obedience. Although students exposed to the exercise had similar gains in learning as those exposed to a control condition, the mean obedience rate was a compelling 95.7%. Furthermore, students self-reported a greater willingness to obey the commands of an authority figure after learning about the Milgram study than before, thereby acknowledging their vulnerability to authority. We discuss the role of Milgram's study in the psychology curriculum and provide recommendations for how this exercise might assist understanding of myriad social psychological principles.